Anesthesia management of carotid body tumour excision - kumara, vijaya (Bali Journal of Anesthesiology, 2019)
Carotid body tumour (CBT) is a rare tumour of chemoreceptor cells, which arises at the bifurcation of the carotid artery. These cells sense the partial pressure of oxygen and carbon dioxide from the blood. Hence, the carotid body plays an important role in the control of ventilation during hypoxia, hypercapnia and acidosis. The tumour arising from these cells is benign and tends to turn out malignant. This tumour is found in persons who live at high altitudes. Removal of tumour poses several anaesthetic challenges and perioperative morbidity or mortality. We report successful anaesthetic management of CBT excision.